2005
DOI: 10.5432/ijshs.3.116
|View full text |Cite
|
Sign up to set email alerts
|

Development of a System to Measure Radius of Curvature and Speed of Hammer Head during Turns in Hammer Throw

Abstract: The aim of this study was to compare the radius of curvature and the estimated head speed as measured by sensors attached to a hammer with those calculated by video image analysis. The participant was the Japanese record holder(83m47). He threw a hammer with sensors which measured the force exerted along the length of the hammer cable using a tension meter made of a metal plate to which strain gauges were affixed, and the angular velocity perpendicular to the hammer cable using two IC accelerometers whose axes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 2 publications
2
20
0
1
Order By: Relevance
“…The general trends of the traces of hammer speed and cable force (Figures 2 and 3) are similar to those previously observed in the literature (Dapena, 1984;Bartonietz et al, 1988;Murofushi et al, 2005;Brice et al, 2008) with the males obtaining higher cable force magnitudes than the females. The trends of the traces of tangential force (Figure 4) are similar to the trend reported by Bartonietz (1994), with the polarity alternating between being positive and negative and there being a single fluctuation within each turn.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The general trends of the traces of hammer speed and cable force (Figures 2 and 3) are similar to those previously observed in the literature (Dapena, 1984;Bartonietz et al, 1988;Murofushi et al, 2005;Brice et al, 2008) with the males obtaining higher cable force magnitudes than the females. The trends of the traces of tangential force (Figure 4) are similar to the trend reported by Bartonietz (1994), with the polarity alternating between being positive and negative and there being a single fluctuation within each turn.…”
Section: Discussionsupporting
confidence: 82%
“…This type of feedback would allow the coach and athlete to formulate a basic assessment of an individual's performance characteristics. For example, previous studies in the literature have shown that generally each peak in hammer speed and cable force is clearly greater in magnitude than the previous peak (Dapena, 1984;Bartonietz et al, 1988;Murofushi et al, 2005;Brice et al, 2008). In this current study this type of behaviour was observed in all but one female (four turner) participant's data.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…We would find that the half of the diameter increases in (SS), and decreases in the (DS) and has an effect on the velocity of the hammer. (18) The relationship between initial and final angular velocities is one of the important factors in the throw movement. Throw technique is effective when a player increases the acceleration from one phase to another to enhance the angular velocity, which transmits in turn to the hammer velocity.…”
Section: Iii-post-measurementmentioning
confidence: 99%